Geomechanical characterization of Newberry Tuff. (September 2016) - Wang, Jihoon; Jung, Woodong; Li, Yawei; Ghassemi, Ahmad
Highlights: Results of a petrophysical and geomechanical characterization program are presented. The work focused on the rock mechanical properties of welded tuffs from Newberry volcano, Oregon. Multistage triaxial compression tests were performed to determine their Young's modulus, Poisson's ratio, and failure envelopes. Multistage triaxial shear tests were performed to determine the mechanical properties and shear strengths of the fractures developed in triaxial compression tests. Joint roughness coefficient (JRC) and Joint Wall Compressive Strength (JCS) were obtained through analysis of the shear tests. The data set obtained in this study is very useful for stimulation design and interpretation of observed micro-seismicity in relation to permeability enhancement. Abstract: In this paper we present the results of a petrophysical and geomechanical characterization program focusing on the rock mechanical properties of welded tuffs from Newberry volcano, Oregon. The rock samples are from drill cores obtained from three wells in the vicinity of the Newberry EGS namely, GEO N-2, GEO N-1, and OXY 72–3. As part of the rock characterization process, petrographic thin sections were prepared and used to describe rock texture and mineralogy. High resolution X-ray CT scanner was also used to provide 3D images of the rock pore structure. Rock porosity and permeability were measured using the gas expansion method and a pulse permeameter, respectively. Triaxial compression tests were performed on the specimens extracted from whole core to determine their Young's modulus, Poisson's ratio, and failure envelopes. In particular, multistage triaxial compression tests were carried out to determine deformation and failure properties, and to establish relationships between petrophysical and mechanical/failure properties. In addition, multistage triaxial shear tests were performed to determine the mechanical properties and shear strengths of the fractures developed in triaxial compression tests. Joint roughness coefficient (JRC) and Joint Wall Compressive Strength (JCS) were obtained through analysis of the shear tests. Joint normal stiffness and shear stiffness were also estimated and it was observed that a higher confining pressure results in higher joint shear stiffness. These studies provide insight into the effects of mineralogy and texture and structure on the strength and deformation properties of the tuff samples tested. Mineral composition and the presence of phenocrysts, argillitic materials, and natural fracture were noted to impact rock mechanical properties. Natural fracture and vein mineralogy also influence fracture development in the samples as well as frictional and shear strength properties of the joints tested. Rock samples with higher clay mineral content were found to be relatively more ductile with minimal increase, or even decrease, in permeability under failure in compression tests. The data set obtained in this study is very useful for stimulation design and interpretation of observed micro-seismicity in relation to permeability enhancement.